How is poststroke fatigue understood by stroke survivors and carers? A thematic analysis of an online discussion forum. Issue 7 (9th July 2019) - Thomas, Karen; Gamlin, Chloe; De Simoni, Anna; Mullis, Ricky; Mant, Jonathan
Abstract : Objective: To understand poststroke fatigue from the perspective of stroke survivors and caregivers expressed in an online discussion forum. Design: The search terms 'tiredness', 'fatigue', 'tired', 'weary' and 'weariness' were used to identify relevant posts. Thematic analysis performed by two independent researchers who coded all forum posts and identified pertinent themes. Posts were coded in relation to two research questions: (1) how is poststroke fatigue described? and (2) what coping strategies are suggested to target poststroke fatigue? Each theme was then summarised by a lead quotation in forum users' own words. Setting: UK-based web forum hosted by Stroke Association, TalkStroke. Archives from 2004 to 2011 were accessed. Participants: 65 stroke survivors and caregivers (mean age 54 years, 61% female) contributed to 89 relevant posts that included a relevant search term. This included 38 stroke survivors, 23 individuals with family or carer role and 4 others unidentified. Results: Six themes were generated: (1) medicalisation of poststroke fatigue: 'a classic poststroke symptom', (2) a tiredness unique to stroke: 'a legacy of stroke', (3) normalisation and acceptance of poststroke fatigue: 'part and parcel of stroke', (4) fighting the fatigue: 'an unwelcome guest', (5) survivors' and caregivers' biological explanations: 'the brain healing' and (6) coping mechanisms: 'pace yourself'. Forum users also repeatedly commented that poststroke fatigue was 'not understood by the profession'. Conclusion: This is the first study to employ data from an online forum to characterise poststroke fatigue. Our data are considered naturalistic owing to the absence of a researcher guiding the discussion and thus generates useful insights for healthcare professionals. Findings suggest a requirement for consistent understanding and explanation to be provided by healthcare professionals. The beliefs outlined here highlight the gap between clinical and community knowledge. Further research to translate understanding of patient and carer perspective into improved management of poststroke fatigue is required.